SEBUAH INFORMASI MUTAKHIR HASIL PENELITIAN TAHUN 2013 DI SITUS KEDATON PLERET, KABUPATEN BANTUL, D.I. YOGYAKARTA - Henki Riko Pratama; Hery Priswanto (Berkala Arkeologi, 2013)
Pleret is one sites that has the Islamic Mataram long way in archaeological research. Pleret existence can not be ignored in a civilization of the Islamic Mataram Period, which also has a parallel position with Kutagede, Kerto, Kartosuro, Surakarta and Yogyakarta. But the glory of pleret was not able to be seen as a whole, only a few partsthat can be met partially. The purpose of writing this article is one of the publications of the result of the research efforts that have been conducted Pleret Kedaton site by displaying the latest findings in the form of the remains of building that are considered part of the building Cepuri keben / ward Srimanganti.